Optimal Damper Slip Force for Vibration Control Structures Incorporating Friction Device with Sway-Rocking Motion Obtained Using Shaking Table Tests - Kazutaka Shirai; Akari Nagaoka; Nami Fujita; Takeshi Fujimori (Advances in Civil Engineering)
In this study, a series of shaking table tests were conducted using a specimen that consisted of a superstructure, incorporating a friction device and a sway-rocking mechanism under the superstructure to determine the optimal damper slip force of a passive vibration control system considering the effects of sway-rocking motion. The adopted simple friction device, composed of rubber bands and stainless steel plates, allowed the magnitude of the slip force to be easily set. The optimal slip force of the friction device, which minimizes the peak and root-mean-square response of the superstructure subjected to earthquakes, was determined from the shaking table tests. Based on the results, the optimal slip force of the friction device was found to vary according to the input level of the ground motions and the sway-rocking conditions. The obtained results suggest that the effect of sway-rocking motion should be considered in the design of passive control structures and the determination of their optimal damper slip force.